Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

Techno-economic performance of an advanced process for synergistic removal of NO/SO2/CO2 via H2O2 pre-oxidation coupled with ammonia scrubbing - Jiaxing Du; Qingqing Liang; Yifan Wang; Hui Xu; Linlin Xu; Yan Liang; Guangying Wang; Lei Bei; Chuanwei Li; Zewei Zhang; Lushi Sun (Fuel, 2027)

hCG orchestrates ovulation in swamp eel (Monopterus albus) via progesterone, metabolic reprogramming, and pyroptosis - Mingsen Zhou; Linlin Wang; Shuo Zheng; Anfu Shen; Xuewen Rao; Liang Ke; Wenhao Hu; Changqing Han; Xiangjiang Liu; Guangfu Hu (Aquaculture, 2027)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Tackling antibiotic resistance genes as environmental contaminants: Innovations in advanced oxidation processes and strategic solutions - Chen Gao; Liang Zhang; Linlin Zang; Hian Kee Lee; Sheng Tang (Journal of Environmental Sciences, 2026)

Metagenomic insights into the distribution and potential influencing factors of antibiotic resistance genes in historically polluted lake sediments - Jinyang Fu; Zhunjie Li; Caixi Hu; Linlin Yao; Mengxi Cao; Yiran Dong; Pu Wang; Yong Liang; Lei Tong; Jianbo Shi (Aquatic Toxicology, 2026)

Tea Rinsing Effectively Mitigates Probabilistic Health Risks From Heavy Metal Exposure - Shuangfei Hu; Linlin Jin; Lili Huang; Cuihong Liu; Minsi Liang; Hongtao Liu (Biological Trace Element Research, 2026)

Prescription principle, phytochemistry, pharmacological activities and clinical applications of Huangqin decoction: a comprehensive review - Yan Fang; Haizhen Liang; Linlin Lu; Xijie Tian; Yuting Zhang; Junyu Zhang; Zhifeng Dai; Xiaojuan Chen; Juan Song; Tao Su; Zhongqiu Liu; Baiping Ma (Phytochemistry Reviews, 2026)

Ecoenzymatic stoichiometry reveals higher microbial nitrogen limitation in active than passive restored alpine wetlands - Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Abraham Allan Degen; Akash Tariq; Feida Sun; Jinchao Gong; Shijie Zhou; Yue Xiu; Linlin Li; Liang Tie; Jordi Sardans; et al. (Journal of Environmental Management, 2026)

Fabrication of aramid nanofiber/silver nanoparticles composite aerogels for enhanced electromagnetic interference shielding - Mingyan Wang; Linlin Cheng; Jinxiao Hou; Shaojuan Chen; Liang Jiang; Yanfen Zhou (Chemical Engineering Journal, 2026)

Impact of environmental factors on the distribution characteristics of phytoplankton functional groups in Beijing - Linlin Qin; Xu Han; Ting Zhu; Yixuan Zhang; Na Cui; Yuepeng Liu; Wenyan Liang (Protist, 2026)

Built-in electric field engineering in boron and bithiophene Co-doped carbon nitride for boosting photodegradation: Mechanism and toxicity assessment - Siyi Wang; Ting Wang; Liang Wang; Tianyu Zhou; Linlin Liu; Chunbo Liu (Journal of Environmental Chemical Engineering, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Compositing high-resolution SDGSAT-1 nighttime light data by ranking of structural image features - Martino Pesaresi; Johannes H. Uhl; Linlin Lu; Panagiotis Politis; Dong Liang; Michele Melchiorri; Inés Marí Rivero; Katarzyna Krasnodębska; Huadong Guo (Remote Sensing of Environment, 2026)

The role of microplastics in bioavailability and toxicity of triclosan in the soil-earthworm system: Inhibitor or facilitator - Xian Chen; Jingcheng Liang; Linlin Shi; Shipeng Luo; Rong Ji; Jiehong Cheng; Ying Wu; Yuchen Wang (Journal of Environmental Chemical Engineering, 2026)

Proteostasis Collapse Drives Effector Memory T Cells Re-expressing CD45RA (TEMRA) Generation in the Tumor Microenvironment - Linlin Li; Shuo Kan; Qiang Huang; Shiwen Wang; Yuchen Han; Liang Chen; Jun Jin (Phenomics, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

Integrating SDGSAT-1 glimmer imagery with Sentinel-1/2 data for high-resolution building height estimation - Zilu Li; Huadong Guo; Linlin Lu; Yifang Ban; Qi Zhu; Dong Liang (Remote Sensing of Environment, 2026)

Decadal climate control of circulation regime transitions in a large marginal sea - Lixia Zheng; Zhongya Cai; Jianping Gan; Chiwing Hui; Linlin Liang; Hiusuet Kung; Zhiqiang Liu (Science Bulletin, 2026)

Hydrodynamics, mixing performance and power consumption in horizontal millimeter-scale helical tube reactors: comprehensive experimental and numerical investigations across a wide range of centrifugal-to-gravitational acceleration ratio - Zhongyao Zhang; Yuanjie Wu; Xiaopeng Chen; Jiezhen Liang; Qianyun Tan; Chenghong Wu; Bo Feng; Denghan Luo; Linlin Wang (Chemical Engineering Journal, 2026)

Interactive effect of children’s copper exposure and socioeconomic status on preschoolers’ cognitive development - Hualong Zhen; Linlin Zhu; Xuemei Hao; Jingru Lu; Yufan Guo; Chunmei Liang; Juan Tong; Fangbiao Tao; Jiong Li; Kun Huang (NeuroToxicology, 2026)

A machine learning-based model for aerosol scattering hygroscopic growth factor (f(RH)) prediction in Beijing urban area - Hongfei Tong; Xinyao Hu; Can Xia; Xiaojing Shen; Yangmei Zhang; Quan Liu; Lei Liu; Linlin Liang; Jiayuan Lu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2026)

Layered circulation and dynamics of the Philippine Sea - Linlin Liang; Jianping Gan; Hiusuet Kung; Chiwing Rex Hui (Progress in Oceanography, 2025)

Aminated lignin-modified polyethersulfone membranes with enhanced antifouling performance for oil-water separation - Linlin Liang; Meijiao Peng; Hui Xu; Zijun Wu; Baojie Liu; Chengrong Qin; Chen Liang; Caoxing Huang; Shuangquan Yao (Journal of Environmental Chemical Engineering, 2025)

Tracking Browning mechanistic pathway of postharvest pine resin using comparative metabolomics - Xin Li; Junsheng Lu; Junmei Ye; Yibin Qin; Xiaopeng Chen; Jiezhen Liang; Linlin Wang (Food Chemistry, 2025)

Hyperbaric oxygen treatment mitigates gut dysbiosis of mice with spinal cord injury - Mo Liu; Lu Yang; Ding Nan; Linlin Ma; Jing Zhang; Fang Liang; Jing Yang; Xuehua Liu (Journal of Molecular Medicine, 2025)

Topographical differentiation characteristics of double high pollution of PM2.5 and ozone in the Beijing-Tianjin-Hebei region - Huan Zhang; Xiaohong Wang; Yiheng Liang; Liyi Qin; Jinlong Li; Linlin Jiao (Air Quality, Atmosphere & Health, 2025)

OA-based photo-Fenton system generates oxidizing and reducing radicals for the simultaneous removal of 1-NA and Cr (VI) in surface waters - Linlin Liang; Li Sun; Qiuwen Wang; Fuqiang Zhang; Huixue Li; Guoquan Liu; Pengfei Wang; Sihui Zhan (Water Research, 2025)

Study on complex failure modes of super-long piles in deep-water and soft-clay seabed under multiple combined loads - Linlin He; Xuan Liu; Yuanshi Xie; Shuting Cao; Yue Liang; Yang Liu (Ocean Engineering, 2025)

Uranium immobilization by Brevundimonas vesicularis LWG1: A synergistic approach via biomineralization, biosorption, and bioreduction - Yanru Liang; Linlin Wang; Panpan Gao; Zichu Qiu; Zemin Qin; Risheng Xu; Yue Li; Wenjuan Shuai; Jimin Li; Xueqing Geng; Hailiang Dong; Yuheng Wang (Journal of Hazardous Materials, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

Ecological niche imprints the structure and network of microbial communities in Lonicera japonica Thunb - Zhaoyu Zhang; Yingda Dong; Xiao Chen; Guozhuang Zhang; Conglian Liang; Yuxin Zhou; Ziying Huang; Liping Shi; Shilin Chen; Linlin Dong; Guangfei Wei (Plant and Soil, 2025)

Occupational exposure to amorphous silica nanoparticles alters lung function and metabolomic features - Xuemin Shi; Chen Liang; LinLin Wang; Xuefeng Bai; Ruiyang Ding; Zhiwei Sun (Toxicology Letters, 2025)

Cross-platform detection of microplastics in human biological tissues: Comparing spectroscopic and chromatographic approaches - Lin Zhang; Jiaqi Tian; Xiaodan Zhu; Linlin Wang; Xiang Yun; Liyang Liang; Shuyin Duan (Journal of Hazardous Materials, 2025)

Crassula perforata structured Ni3S2/NiTe electrodes enable efficient and robust seawater electrolysis at industrial-level current density - Xueling Wei; Xiangyu Zou; Qiguan Wang; Qiannan Liang; Youjun Huang; Taotao Ai; Wenhu Li; Linlin Dang; Sumin Wang (Fuel, 2025)

Resin tapping in Masson pine (Pinus massoniana): Response of resin yield and its product quality to film mulching and chemical stimulation treatments - Jiaqi Liang; Xiaopeng Chen; Linlin Wang; Xiaojie Wei; Kewei Mo; Zehui Xiong; Jiezhen Liang (Biomass and Bioenergy, 2025)

Insight into peroxidase-mediated Pinus massoniana resin browning, and browning inhibition strategy - Hanxiao Liu; Xiaopeng Chen; Dandan Yu; Siheng Zhang; Jiezhen Liang; Xin Li; Xiaojie Wei; Linlin Wang (Sustainable Chemistry and Pharmacy, 2025)

Huge challenges of improving ozone pollution in China: High regional background ozone concentrations calculated from observational data - Yusi Liu; Yang Zhang; Fan Yang; Linlin Liang; Guiqian Tang (Environmental Pollution, 2025)

Oxygenated volatile organic compounds in Beijing: Characteristics, chemical reactivity, and source identification - Gen Zhang; Xiaoqi Zhou; Yifeng Sun; Chong Han; Jiyun Xian; Changxu Mu; Wanyun Xu; Linlin Liang (Environmental Pollution, 2025)

Studying the Impact of the Load Distribution Ratio on the Unsteady Performance of a Dual-Stage Pump-Jet Propulsor - Jiansheng Zhang; Ning Liang; Jianwei Zhang; Linlin Cao; Dazhuan Wu; Wei Zhao; Hanqiao Han (Journal of Marine Science and Engineering, 2025)
This study investigated the impact of different load distribution ratios between two rotors on the unsteady performance of dual-stage pump-jet propulsors using Computational Fluid Dynamics (CFDs) and experimental methods. The Shear Stress Transport (SST) k-ω model was employed to solve turbulence problems, and the numerical simulation method used was validated. The following conclusions were drawn: Different load distribution ratios of the dual-stage rotors have no significant impact on the overall propulsion performance of the propulsor. As the load distribution ratio is aft-shifted, the axial unsteady force of the entire propulsor continuously decreases, with a reduction of up to 53.6%. This is due to the gradual reduction in the energy of the first-stage rotor, leading to a more uniform Blade-Passing Frequency Velocity Harmonic Coefficient (BPFVHC) in front of the second-stage rotor, thereby gradually reducing the unsteady force of the second-stage rotor. The experimental results also indicate that the aft-shifted load model can reduce the sound pressure level of the propulsor. Compared to the prototype propulsor, the sound pressure level at the Blade-Passing Frequency decreases by 6.67 dB, or about 78.5%, in sound energy. This study has important implications for the low-excitation design of dual-stage pump-jet propulsors.

Innovative citric acid/polydopamine@sepiolite composites for efficient removal of Ni2+ and methylene blue in single and binary adsorption systems: Regulation and mechanism - Linlin Liang; Zefeng Ge; Wu Lei; Fengyun Wang; Mingzhu Xia; Zhihui Wang (Journal of Environmental Chemical Engineering, 2025)

Functionality-dependent removal efficiency and mechanisms of polystyrene microplastics by a robust magnetic biochar - Xiaotong Duan; Xian Chen; Linlin Shi; Yiran Cao; Yuechang Liang; Tianyu wang; Chen Huang; Yuxin Cao (Journal of Environmental Chemical Engineering, 2025)

Identification and characterization of ClAPRR2, a key candidate gene controlling watermelon stripe color - Shuang Liang; Miaomiao Yang; Linlin Zhang; Xufeng Fang; Xian Zhang; Chunhua Wei; Zuyun Dai; Zhongzhou Yang; Chaonan Wang; Bin Liu; Feishi Luan; Shi Liu (Plant Science, 2025)

Corrigendum to “The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments” [166 (2024) 106937] - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2025)

Optimization model for co-pyrolytic synergy: A case study in starch sludge with chicken manure and comprehensive investigation combining kinetics, bio-products characterization, and DFT-based decomposition pathways - Hairong Mo; Xiaopeng Chen; Tongxi Mo; Chenghong Wu; Wanbin Wei; Yuanjie Wu; Qinxin Li; Jiezhen Liang; Linlin Wang (Fuel, 2025)

Migration of depleted uranium from a corroded penetrator in soil vadose zone in Bosnia and Herzegovina - Cui Li; Yanru Liang; Yin Ye; Fan Chen; Markus Astner; David J. Paterson; Yanlong Chen; Linlin Wang; Paul Guagliardo; Matvei Aleshin; Mario Burger; Peter M. Kopittke; et al. (Journal of Hazardous Materials, 2024)

Construction of covalent electrode/solid electrolyte interface for stable flexible solid-state lithium batteries - Junlong Zou; Linlin Wang; Jun Zhang; Qiyue Sun; Yongyin Wang; Mingtao Zheng; Yong Xiao; Hang Hu; Yingliang Liu; Yeru Liang (Chemical Engineering Journal, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2024)

Recent Holocene activity and regional tectonic significance of the northern segment of the red river fault zone - Long Guo; Zhongtai He; Zhikun Ren; Linlin Li; Xingao Li; Haomin Ji; Kuan Liang; Xin Tan (Journal of Structural Geology, 2024)

Variation characteristics of fluorescent biological aerosol particles in Beijing under springtime clean, haze and dusty condition - Linlin Liang; Wanyun Xu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Yangmei Zhang; Junying Sun (Urban Climate, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Photosynthetic microalgae microbial fuel cells for bioelectricity generation and microalgae lipid recovery using Gd-Co@N-CSs/NF as cathode - Linlin Qin; Yiming Qin; Na Cui; Xu Han; Haoran Lu; Tong Yang; Wenyan Liang (Chemical Engineering Journal, 2024)

Editorial: The response, adaptation, and evolution of marine molluscs - Xiao Liang; Linlin Zhang; Yingxiang Li (Frontiers in Marine Science, 2024)

EB-Net: an efficient balanced network for accuracy and speed of remote sensing detection - Dehua Zhang; Dechen Wang; Changcheng Yu; Xinyuan Hao; Linlin Liang (International Journal of Remote Sensing, 2024)

A review of indoor nitrous acid (HONO) pollution: Measurement techniques, pollution characteristics, sources, and sinks - Chang Liu; Linlin Liang; Wanyun Xu; Qingxin Ma (Science of The Total Environment, 2024)

Magnetite alleviating calcification of anaerobic granular sludge (AnGS): Electron transfer enhancement and ion competition - Linlin Chen; Ruoxuan Yuan; Xiangyang Xu; Liang Zhu (Science of The Total Environment, 2024)

Numerical investigation of microbubble drag reduction on an axisymmetric body based on Eulerian multiphase model - Xuanhao Shao; Ning Liang; Shijie Qin; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2024)

Influence of meteorological factors on open biomass burning at a background site in Northeast China - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Journal of Environmental Sciences, 2024)

Influence paradigms of soil moisture on land surface energy partitioning under different climatic conditions - Xiao Chen; Zhihua Pan; Binxiang Huang; Ju Liang; Jialin Wang; Ziyuan Zhang; Kang Jiang; Na Huang; Guolin Han; Buju Long; Zhenzhen Zhang; Jingyu Men; et al. (Science of The Total Environment, 2024)

Observational insights into the environmental effect for secondary inorganic aerosol formation in the Northeast China: Influence of biomass burning - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Atmospheric Research, 2024)

Construction of a methodology framework to characterize dynamic full-sector land-use carbon emissions embodied in trade - Yuhan Ke; Linlin Xia; Ruwei Wang; Sai Liang; Zhifeng Yang (Science of The Total Environment, 2024)

N-methyl pyrrolidone manufacturing wastewater as the electron donor for denitrification: From bench to pilot scale - Songyun Chen; Xiaohui Zhu; Ge Zhu; Bin Liang; Jin Luo; Danyang Zhu; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (Science of The Total Environment, 2024)

Electrocatalytic degradation of nitrogenous heterocycles on confined particle electrodes derived from ZIF-67 - Yu Liu; Linlin Qin; Yiming Qin; Tong Yang; Haoran Lu; Yulong Liu; Qiqi Zhang; Wenyan Liang (Journal of Hazardous Materials, 2024)

A comprehensive study on the co-removal of Cr (VI) and ciprofloxacin via microbial-photocatalytic coupling: Mechanistic insights and performance evaluation - Yilin Dong; Qiuwen Wang; Jinyu Zhu; Linlin Liang; Dongyu Xu; Xueyue Mi; Zhijun Ren; Pengfei Wang (Journal of Environmental Management, 2024)

Comprehensive analyses of annexins in naked carp (Gymnocypris przewalskii) unveil their roles in saline-alkaline stress - Linlin A; Yujing Zhang; Baoke Xu; Haichen Zhang; Yixin Li; Le Wang; Jian Liang; Weiguo Zhou; Zhaohui Feng; Hong Zhang (Aquaculture, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

China's economic restructuring reduced emissions of polycyclic aromatic hydrocarbons (PAHs) in the post-global financial crisis era - Linlin Xia; Jianbing Wang; Ruwei Wang; Sai Liang; Zhifeng Yang (Journal of Cleaner Production, 2024)

Influence of sampling location and processing on the assembly and network of Polygoni Multiflori Radix surface microbiome - Guangfei Wei; Yichuan Liang; Guozhuang Zhang; Zhaoyu Zhang; Yongqing Zhang; Shilin Chen; Linlin Dong (International Journal of Food Microbiology, 2024)

Fabrication and mechanism of La/Al bimetallic organic frameworks for phosphate removal - Zheng Zhu; Linlin Qin; Yulong Liu; Qiqi Zhang; Peng Cheng; Wenyan Liang (Chemical Engineering Journal, 2024)

Effect mechanisms of leading-edge tubercle on blade cavitation control in a waterjet pump - Guoshou Zhao; Ning Liang; Qianqian Li; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2023)

A novel lateral epitaxial Bi2O3@BiOCl heterostructure for photocatalytic antibiotic degradation in an internal circulation fluidized bed reactor - Yilin Dong; Shaoxuan Pang; Fuqiang Zhang; Dongyu Xu; Qiuwen Wang; Kang Wang; Lijun Zhang; Linlin Liang; Zhijun Ren; Pengfei Wang (Chemical Engineering Journal, 2023)

Depth investigation of the regulation mechanism of SiO2 on the denitrification performance and sulfur resistance of MnCe/Ti SCR catalyst - Mengxia Qing; Linlin Zhang; Liang Liu; Yaxin Chen; Yunda Su; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2023)

Frequency specific alterations of the degree centrality in patients with acute basal ganglia ischemic stroke: a resting-state fMRI study - Hao Chen; Linlin Zhan; Qianqian Li; Chaoguo Meng; Xuemei Quan; Xiaoling Chen; Zeqi Hao; Jing Li; Yanyan Gao; Huayun Li; Xize Jia; Mengting Li; et al. (Brain Imaging and Behavior, 2023)
This study intended to investigate the frequency specific brain oscillation activity in patients with acute basal ganglia ischemic stroke (BGIS) by using the degree centrality (DC) method. A total of 34 acute BGIS patients and 44 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (rs-fMRI) scanning. The DC values in three frequency bands (conventional band: 0.01–0.08 Hz, slow‑4 band: 0.027–0.073 Hz, slow‑5 band: 0.01–0.027 Hz) were calculated. A two-sample t -test was used to explore the between-group differences in the conventional frequency band. A two-way repeated-measures analysis of variance (ANOVA) was used to analyze the DC differences between groups (BGIS patients, HCs) and bands (slow‑4, slow‑5). Moreover, correlations between DC values and clinical indicators were performed. In conventional band, the DC value in the right middle temporal gyrus was decreased in BGIS patients compared with HCs. Significant differences of DC were observed between the two bands mainly in the bilateral cortical brain regions. Compared with the HCs, the BGIS patients showed increased DC in the right superior temporal gyrus and the left precuneus, but decreased mainly in the right inferior temporal gyrus, right inferior occipital gyrus, right precentral, and right supplementary motor area. Furthermore, the decreased DC in the right rolandic operculum in slow-4 band and the right superior temporal gyrus in slow-5 band were found by post hoc two-sample t -test of main effect of group. There was no significant correlation between DC values and clinical scales after Bonferroni correction. Our findings showed that the DC changes in BGIS patients were frequency specific. Functional abnormalities in local brain regions may help us to understand the underlying pathogenesis mechanism of brain functional reorganization of BGIS patients.

Improved biomass burning pollution in Beijing from 2011 to 2018 - Linlin Liang; Zhenyu Du; Guenter Engling; Xuyan Liu; Wanyun Xu; Chang Liu; Yuan Cheng; Dongsheng Ji; Gen Zhang; Junying Sun (Atmospheric Environment, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Occurrence of fungi and mycotoxins in herbal medicines and rapid detection of toxin-producing fungi - Guangfei Wei; Xiaotong Guo; Yichuan Liang; Congsheng Liu; Guozhuang Zhang; Conglian Liang; Zhixin Huang; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Pollution, 2023)

Identifying the O3 chemical regime inferred from the weekly pattern of atmospheric O3, CO, NOx, and PM10: Five-year observations at a center urban site in Shanghai, China - Gen Zhang; Yifeng Sun; Wanyun Xu; Lingyan Wu; Yuseng Duan; Linlin Liang; Yuan Li (Science of The Total Environment, 2023)

Corrigendum to “Self-assembly of Fe3O4 with natural tannin as composites for microalgal harvesting” [Fuel 321 (2022) 124038] - Xiaoyu Wang; Chuang Liu; Linlin Qin; Wenyan Liang (Fuel, 2023)

Strategies for mapping protein hydrolysate profiles and pharmacokinetics based on non-targeted proteomics combining skyline-aided quantitative techniques - Shuying Mao; Wei Jin; Sisi Fu; Keanqi Liu; Feng Xu; Linlin Wu; Yexin Xu; Huizhu Yang; Huafang Liu; Guangji Wang; Yan Liang (Analytica Chimica Acta, 2023)

Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites - Shiyu Li; Lin Yang; Jialong Wu; Linlin Yao; Deming Han; Yong Liang; Yongguang Yin; Ligang Hu; Jianbo Shi; Guibin Jiang (Water Research, 2023)

MOF-templated fabrication of Ni@C/g-C3N4 catalyst with high-dense accessible active sites achieving dicyclopentadiene hydrogenation at ambient conditions and comprehensive mechanism insight - Chenghong Wu; Xiaopeng Chen; Jiezhen Liang; Jiawei Fu; Zhongyao Zhang; Xiaojie Wei; Linlin Wang (Chemical Engineering Journal, 2023)

A Tiered Ecological Risk Assessment of Caffeine by Using Species Sensitivity Distribution Method in the Nansi Lake Basin - Lei Zheng; Juan Zhang; Yinan Wu; Linlin Li; Junhong Ling; Sai Wang; Wenlong Yang; Yezhu Yin; Liang Dong; Yizhang Zhang (Bulletin of Environmental Contamination and Toxicology, 2023)

Origins of black carbon from anthropogenic emissions and open biomass burning transported to Xishuangbanna, Southwest China - Xuyan Liu; Siwen Wang; Qianqian Zhang; Chunlai Jiang; Linlin Liang; Shihao Tang; Xingying Zhang; Xiuzhen Han; Lin Zhu (Journal of Environmental Sciences, 2023)

Understanding the N-acylated homoserine lactones(AHLs)-based quorum sensing for the stability of aerobic granular sludge in the aspect of substrate hydrolysis enhancement - Zhiming Zhang; Linlin Wang; Yatong Ji; Runjuan Cao; Jiaheng Zhou; Mengyan Li; Liang Zhu; Xiangyang Xu (Science of The Total Environment, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

Metagenomic and extracellular polymeric substances analysis reveals the mechanism of exogenous N-hexanoyl-L-homoserine lactone in alleviating the inhibition of perfluorooctanoic acid on anammox process - Linqin Tang; Chengyuan Su; Cuiping Fan; Linlin Cao; Zhu Liang; Yufeng Xu; Zhengpeng Chen; Qing Wang; Menglin Chen (Bioresource Technology, 2023)

Investigation of the mechanism of copy number variations involving the α-globin gene cluster on chromosome 16: two case reports and literature review - Dina Zhu; Linlin Xu; Yanxia Zhang; Guanxia Liang; Xiaofeng Wei; Liyan Li; Wangjie Jin; Xuan Shang (Molecular Genetics and Genomics, 2023)

Health risk assessment of As due to rice ingestion based on iAs distribution and actual consumption patterns for the residents in Beijing: a cross-sectional study - Suzhen Cao; Qi Cao; Kan Shao; Yijin Kang; Weigang Liang; Linlin Zhang; Juan Wang; Ning Qin; Xiaoli Duan (Environmental Geochemistry and Health, 2022)

Radioactivity of Strontium-90 in Soil Samples Along the Hai River in Tianjin, China - Fei Chen; Linlin Yan; Qiang Xiong; Xiao Ge; Jing Liang; Zhen Zhang; Shengyuan Yang; Ling Jiao (Water, Air, & Soil Pollution, 2022)

Salt sealing induced in situ N-doped porous carbon derived from wheat bran for the removal of doxycycline from aqueous solution - Linlin Liang; Xinyong Niu; Xiuli Han; Chun Chang; Junying Chen (Environmental Science and Pollution Research, 2022)

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

Characterizing the Semi-Volatile Organic Compounds in Runoff from Roads and Other Impervious Surfaces in a Suburban Area of Beijing - Liang Zhang; Haiyan Li; Youshu Wang; Zhichao Yang; Ziyang Zhang; Fei Liu; Linlin Tong; Ying Wang; Yongwei Gong; Hua Yang (Archives of Environmental Contamination and Toxicology, 2022)

Intensification of Downslope Nutrient Transport and Associated Biological Responses Over the Northeastern South China Sea During Wind-Driven Downwelling: A Modeling Study - Aiqin Han; Jianping Gan; Minhan Dai; Zhongming Lu; Linlin Liang; Xiaozheng Zhao (Frontiers in Marine Science, 2021)
Coastal downwelling is generally considered to have a limited biological effect compared with coastal upwelling. In this study, downslope transport of nearshore, nutrient-enriched waters during downwelling is found to induce distinct biological productivity in the water column over the northeastern South China Sea (NSCS). By conducting a process-driven study over a widened shelf with intensified downwelling in the NSCS, we investigated the biophysical processes associated with strong nutrient enrichment in the water column of downwelled waters. These processes and underlying mechanisms are largely unreported and remain unclear. Field measurements and a three-dimensional coupled physical-biological model incorporating nitrate ( N ), phytoplankton ( P ), zooplankton ( Z ), and detritus ( D ) were utilized to investigate distinct cross-shore nutrient transport over the uniquely widened NSCS shelf. We revealed that intensified downwelling circulation, dynamically induced by the widened shelf topography, enhanced chlorophyll a and biological productivity in a strip of well-mixed water over the inner shelf as well as in the downwelled water over the mid-shelf. Strong time lags and spatial differences existed among N , P , and Z because of the physical transport and the ensuing biogeochemical response. The intensified downslope transport of nutrient-rich coastal water formed distinct cross-shore wedge-shaped P , Z , and D structures, while N was rapidly consumed in the water column. This study illustrates the underlying coupled physical-biogeochemical processes associated with the observed biogeochemical response to wind-driven downwelling circulation over the variable shelf, which are commonly found in coastal oceans worldwide.

Tissue distribution of transcription for 29 lipid metabolism-related genes in Takifugu rubripes, a marine teleost storing lipid predominantly in liver - Houguo Xu; Xiaoxue Meng; Linlin Jia; Yuliang Wei; Bo Sun; Mengqing Liang (Fish Physiology and Biochemistry, 2020)

Cloning and Characterization of Cholesterol 25-Hydroxylase (ch25h) From a Marine Teleost, Chinese Tongue Sole (Cynoglossus semilaevis), and Its Gene Expressions in Response to Dietary Arachidonic Acid - Houguo Xu; Bo Sun; Linlin Jia; Yuliang Wei; Zhangbin Liao; Mengqing Liang (Frontiers in Marine Science, 2020)

Influence of High Relative Humidity on Secondary Organic Carbon: Observations at a Background Site in East China - Linlin Liang; Guenter Engling; Yuan Cheng; Xiaoye Zhang; Junying Sun; Wanyun Xu; Chang Liu; Gen Zhang; Hui Xu; Xuyan Liu; Qianli Ma (Journal of Meteorological Research, 2019)

Major ion and dissolved heavy metal geochemistry, distribution, and relationship in the overlying water of Dongting Lake, China - Yan Chen; Lingqing Wang; Tao Liang; Jun Xiao; Jing Li; Haicheng Wei; Linlin Dong (Environmental Geochemistry and Health, 2019)

A study of the coupled bioelectrochemical system-upflow anaerobic sludge blanket for efficient transformation of 2,4-dichloronitrobenzene - Hui Chen; Donghui Lu; Linlin Chen; Caiqin Wang; Xiangyang Xu; Liang Zhu (Environmental Science and Pollution Research, 2019)

Effect of supersaturation on the oral bioavailability of paclitaxel/polymer amorphous solid dispersion - Linlin Miao; Yuheng Liang; Wenli Pan; Jingxin Gou; Tian Yin; Yu Zhang; Haibing He; Xing Tang (Drug Delivery and Translational Research, 2019)

A transposition-active Phyllostachys edulis long terminal repeat (LTR) retrotransposon - Mingbing Zhou; Linlin Liang; Heikki Hänninen (Journal of Plant Research, 2018)

An integrated approach for water scarcity evaluation—a case study of Yunnan, China - Hongrui Wang; Linlin Fan; Yuan Liang; Cheng Wang (Environment, Development and Sustainability, 2018)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

NF45 overexpression is associated with poor prognosis and enhanced cell proliferation of pancreatic ductal adenocarcinoma - Chunhua Wan; Chen Gong; Li Ji; Xiaorong Liu; Yayun Wang; Liang Wang; Mengting Shao; Linlin Yang; Shaoqing Fan; Yin Xiao; Xiaotong Wang; Manhua Li; et al. (Molecular and Cellular Biochemistry, 2015)

Stromal cell-derived factor 1 (SDF-1) accelerated skin wound healing by promoting the migration and proliferation of epidermal stem cells - Rui Guo; Linlin Chai; Liang Chen; Wenguang Chen; Liangpeng Ge; Xiaoge Li; Hongli Li; Shirong Li; Chuan Cao (In Vitro Cellular & Developmental Biology - Animal, 2015)

Highly sensitive fluorescence biosensors for sparfloxacin detection at nanogram level based on electron transfer mechanism of cadmium telluride quantum dots - Wanjun Liang; Shaopu Liu; Jing Song; Chenxia Hao; Linlin Wang; Dan Li; Youqiu He (Biotechnology Letters, 2015)

Erratum to: Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effects of Exogenous Salicylic Acid and Nitric Oxide on Physiological Characteristics of Perennial Ryegrass Under Cadmium Stress - Quanhui Wang; Xue Liang; Yuanjie Dong; Linlin Xu; Xiuwei Zhang; Jing Kong; Shuang Liu (Journal of Plant Growth Regulation, 2013)

Effect of mechanical stretch on the expressions of elastin, LOX and Fibulin-5 in rat BMSCs with ligament fibroblasts co-culture - Zhao Bing; Liang Linlin; Yan Jianguo; Ren Shenshen; Ren Ruifang; Zhang Xi (Molecular Biology Reports, 2012)

PTEN inhibits proliferation and functions of hypertrophic scar fibroblasts - Liang Guo; Liang Chen; Sheng Bi; Linlin Chai; Zengxiang Wang; Chuan Cao; Ling Tao; Shirong Li (Molecular and Cellular Biochemistry, 2012)

Determination of Phthalate Esters in Soil Samples by Microwave Assisted Extraction and High Performance Liquid Chromatography - Pei Liang; Linlin Zhang; Lili Peng; Qian Li; Ehong Zhao (Bulletin of Environmental Contamination and Toxicology, 2010)